PENGEMBANGAN INTEGRASI NILAI-NILAI FILOSOFI KAIN TAPIS UNTUK MENINGKATKAN KESADARAN BUDAYA PADA MAHASISWA PENDIDIKAN SEJARAH UNIVERSITAS LAMPUNG - Istiani, Yuni; Agung, Leo; Sariyatun, S (HISTORIKA, 2017)
Tapis was the one of traditional cloth that contained in Lampung society. There was a philosophy values that contained in some kind of the pattern of Tapis. This study aimed to; (1) a. know the learning model of Lampung Culture that have been implemented; b. know the needs of the learning model of Lampung Culture; c. know how big the culture awareness of the students in History Education Study Program of University of Lampung; (2) Develop a learning model to integrate the philosophy values of Tapis in Lampung Culture at History Education Study Program of University of Lampung ; (3) Assess the effectiveness of learning model to integrate the philosophy values of Tapis on the learning the Lampung Culture to improve the culture awereness of History Education students. This research used the developmental research method (Research and Development/R&D). The method was used to produce some product and examine the effectiveness of those product. To be able to produce the product, the requirement analysis research was used in this research to examine the effectiveness of the product in order to serve the function in the society. This research was held at the sixth semester students of History Education Study Program. There were two classes; A class as a experimental class and B class as a control class. This research was held of the even semester in the school year 2015/2016. The result of the effectiveness of the achievement (cognitieve) showed there was a significant difference in students’ ability between experimental and control class. The result showed the score of t value 8.557 in the level of significant 0.78 was higher than 0.05 (0.78 > 0.05). It could be conclude that experimental and control class were not in the same varian and the mean competence also was not same. The result of t value in the attitude assessment showed the score of thit (2.015) >ttab (1.678) in the level of significant 0.02 was lower than 0.05 (0.02 < 0.05), it could be conclude that Ho was rejected and the mean score before and after the treatement to the experimental class was not same. The result indicate that there was a significanct influence of the learning model of Lampung culture based on the philosophy values of Tapis to improve the Culture Awereness of the students. In conclusion, the integration development of the philosophy values of Tapis on the leaarning model in Lampung culture was effective to improve learning outcomes and the culture awereness of the students.